Peningkatan Kinerja Campuran Beraspal Panas dengan Penggunaan Aspal Modifikasi Zeolit - Ratna Yuniarti; Made Mahendra; I Dewa Made Alit Karyawan; Desi Widianty; Fera Fitri Salsabila; Fauzi Gusnaldi; Erlina Erlina (LPPM Universitas Mataram, 2025)
Damage to road pavement construction before reaching its planned lifespan can be caused by asphalt being easily oxidized and vulnerable to sunlight exposure. Therefore, materials resistant to high temperatures should be used. One effort that can be done is modifying asphalt with zeolite. Zeolite contains silica, which can increase the binding strength between asphalt and aggregate and reduce the sensitivity of asphalt to temperature. The aim of this study is to analyze the characteristics of zeolite-modified asphalt with 3%, 5%, and 7% of the modified asphalt weight and its performance when applied to hot-mix asphalt. Asphalt characteristic tests include penetration tests, softening points, flash points, ductility, loss on heating, and specific gravity. Hot mix asphalt tests include the ability of the mixture to withstand loading, melting, Marshall quotient, Marshall immersion, and retained stability index. Based on the analysis, it can be concluded that the use of zeolite as an asphalt modifier increases the resistance to temperature changes of modified asphalt. The performance of hot-mix asphalt improved when using zeolite-modified asphalt compared to traditional asphalt mixtures. The recommended percentage of zeolite is 5% of the weight of modified asphalt, and the residual strength index achieved is 91.1%.